2020
DOI: 10.3390/a13110305
|View full text |Cite
|
Sign up to set email alerts
|

Searching via Nonlinear Quantum Walk on the 2D-Grid

Abstract: We provide numerical evidence that the nonlinear searching algorithm introduced by Wong and Meyer, rephrased in terms of quantum walks with effective nonlinear phase, can be extended to the finite 2-dimensional grid, keeping the same computational advantage with respect to the classical algorithms. For this purpose, we have considered the free lattice Hamiltonian, with linear dispersion relation introduced by Childs and Ge The numerical simulations showed that the walker finds the marked vertex in O(N1/4log3/4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Meyer and Gong study quantum search with the Gross-Pitaevskii equation [75,76] concluding that it solves the unstructured search problem more efficiently than does the Schrödinger equation, because it includes a cubic nonlinearity, and Chiew et al [77] demonstrate that the nonlinear quantum search can be more efficient than quantum search for graph comparison. Di Molfetta and Herzog [78] generalize the Meyer-Gross algorithm to two dimensions finding a clear advantage over the linear QW. Finally, in [79] the thresholds between modulational stability, rogue waves and soliton regimes are studied with coupled nonlinear Schrödinger equations with on site saturating nonlinearity.…”
Section: Nonlinear Dqwmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer and Gong study quantum search with the Gross-Pitaevskii equation [75,76] concluding that it solves the unstructured search problem more efficiently than does the Schrödinger equation, because it includes a cubic nonlinearity, and Chiew et al [77] demonstrate that the nonlinear quantum search can be more efficient than quantum search for graph comparison. Di Molfetta and Herzog [78] generalize the Meyer-Gross algorithm to two dimensions finding a clear advantage over the linear QW. Finally, in [79] the thresholds between modulational stability, rogue waves and soliton regimes are studied with coupled nonlinear Schrödinger equations with on site saturating nonlinearity.…”
Section: Nonlinear Dqwmentioning
confidence: 99%
“…where there is a dependence on the values of the walker in both dimensions. It was discussed in [78] that non-linear QWs, that introduce the nonlinearity in form of phases on the walker components, can be exploited to perform efficient search tasks on the two-dimensional grid. In line with those findings, we observed that the NLQW that introduces nonlinearities in the coin rotation operator angle produces ballistic dispersion, indicating that no soliton-like structures are formed in the two-dimensional case.…”
Section: No Solitons In 2dmentioning
confidence: 99%
“…Quantum nonlinearity, beyond the stochastic nonlinearity provided by projective measurement, might be a powerful computational resource. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, there is no experimental evidence for physics beyond standard linear quantum mechanics. [18][19][20][21] It is well known to be challenging to even formulate a consistent, fundamentally nonlinear quantum theory in accordance with general principles.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: nonlinear channels, non-completely positive channels, Bloch vector amplification (Some figures may appear in colour only in the online journal) Several papers have explored the use of real or effective quantum nonlinearity for information processing [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Nonlinear master equations have also been frequently discussed in open systems theory [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%